Profanations - Agamben, Giorgio (Zone Books, 2007)
Genius -- Magic and happiness -- Judgment day -- The assistants -- Parody -- Desiring -- Special being -- The author as gesture -- In praise of profanation -- The six most beautiful minutes in the history of cinema